KCNQ5 and C9orf50 Methylation in Stool DNA for Early Detection of Colorectal Cancer - Cao, Yaping; Zhao, Guodong; Yuan, Mufa; Liu, Xiaoyu; Ma, Yong; Cao, Yang; Miao, Bei; Zhao, Shuyan; Li, Danning; Xiong, Shangmin; Zheng, Minxue; Fei, Sujuan (Frontiers in Oncology, 2021)
Background Aberrant DNA methylation has emerged as a class of promising biomarkers for early colorectal cancer (CRC) detection, but the performance of methylated C9orf50 and methylated KCNQ5 in stool DNA has never been evaluated. Methods Methylation specific quantitative PCR (qPCR) assays for methylated C9orf50 and methylated KCNQ5 were developed. The methylation levels of C9orf50 and KCNQ5 in 198 CRC patients, 20 advanced adenoma (AA) patients, 101 small polyp (SP) patients, and 141 no evidence of disease (NED) subjects were analyzed. Results The methylation levels of both KCNQ5 and C9orf50 genes were significantly higher in CRC and AA groups than those in SP and NED groups, but showed no significant difference among different stages of CRC. The sensitivities of methylated KCNQ5 and methylated C9orf50 for CRC detection were 77.3% (95% CI: 70.7–82.8%) and 85.9% (95% CI: 80.0–90.2%) with specificities of 91.5% (95% CI: 85.3–95.3%) and 95.0% (95% CI: 89.7–97.8%), respectively. When C9orf50 and methylated KCNQ5 were combined, the clinical performance for CRC detection was similar to that of methylated C9orf50 alone. Conclusions Stool DNA based methylated C9orf50 test has the potential to become an alternative approach for CRC screening and prevention.